PUBLIC PERCEPTION OF THE EXISTENCE OF METRO CITY SLAUGHTERHOUSES - Novia Ambar Sari (KaliAgri Journal, 2025)
The public perception of the existence of the Animal Slaughterhouse Regional Technical Implementation Unit (UPTD RPH) under the Department of Food Security, Agriculture, and Fisheries of Metro City can be defined as the responses of interacting individuals influenced by positive or negative values derived from norms or customs, which are received through the sensory system and interpreted by the nervous system in the brain. This study was conducted to identify the positive and negative perceptions of the community regarding the presence of the slaughterhouse in Metro City. The sampling method employed in this research was saturated sampling (census). The sampling technique used was Purposive Sampling, with the consideration that the respondents' residences are located within a maximum distance of 100 meters from the Metro City Slaughterhouse. The respondents were categorized into two groups: the first group consists of those living 0–50 meters from the facility, and the second group consists of those living 51–100 meters away. Qualitative data analysis was utilized as the analytical technique. The results of this study indicate that the community's positive perception of the UPTD Slaughterhouse is that it is quite beneficial. Conversely, regarding negative perceptions, the community finds the odor quite disturbing, while water pollution and waste from the slaughterhouse are considered not disturbing at all.